Assessment of Risk Factors and Prevalence of Musculoskeletal Disorders in staff members of Imam Khomeini Hospital in Shirvans Using REBA Method - Rajabali HOKMABADI; Hossein EBRAHIMIAN; Mohammad Hossein ASGHARI; Zeinab REZAEE (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Working in difficult and uncomfortable conditions for a long time causes musculoskeletal disorders. Prevention of these disorders requires assessment and correction of working conditions using occupational analysis methods of ergonomic science. Therefore, this study aims to evaluate the staff working posture in the hospital. Methods: This descriptive-analytic study was conducted in 1394 among 237 staffs of Imam Khomeini Hospital in Shirvan. The prevalence of musculoskeletal disorders was assessed using the Nordic questionnaire as well as the assessment of staff posture status by REBA method. Data were analyzed by SPSS 18 software. Results: There were 237 participants in the study, 45 of which were male (19%) and 192 of them were female (81%). The mean age of subjects is 32.19 ± 7.8 years and the average work experience is 6.87 ± 6.7 years. The highest prevalence of musculoskeletal disorders was in the waist (68.4%) and knee (59.9%). According to REBA rating, about 3% of tasks require necessary reforms, 36% of tasks need to be reformed as soon as possible, and 61% of tasks require immediate reforms. The prevalence of musculoskeletal disorders had a significant relationship with sex, work experience and age. Conclusion: The results of the study showed that the majority of work tasks need to be corrected. Several activities such as raising work level, personnel training, having work rest, exercising and appropriate training are essential